Conference Report: The 3rd Global CRO Council for Bioanalysis at the International Reid Bioanalytical Forum. (December 2011) - Breda, Massimo; Garofolo, Fabio; Caturla, Maria Cruz; Couerbe, Philippe; Maltas, John; White, Peter; Struwe, Petra; Sangster, Timothy; Riches, Suzanne; Hillier, Jim; Garofolo, Wei; Zimmerman, Thomas; et al.
The 3rd Global CRO Council Closed Forum was held on the 3rd and 4th July 2011 in Guildford, United Kingdom, in conjunction with the 19th International Reid Bioanalytical Forum. In attendance were 21 senior-level representatives from 19 CROs on behalf of nine European countries and, for many of the attendees, this occasion was the first time that they had participated in a GCC meeting. Therefore, this closed forum was an opportunity to increase awareness of the aim of the GCC and how it works, share information about bioanalytical regulations and audit findings from different agencies, their policies and procedures and also to discuss some topics of interest and aim to develop ideas and provide recommendations for bioanalytical practices at future GCC meetings in Europe.